Uncovering the role of mitochondrial genome in pathogenicity and drug resistance in pathogenic fungi - Ni, Yue; Gao, Xindi (Frontiers in Cellular and Infection Microbiology, 2025)
Fungal infections are becoming more prevalent globally, particularly affecting immunocompromised populations, such as people living with HIV, organ transplant recipients and those on immunomodulatory therapy. Globally, approximately 6.55 million people are affected by invasive fungal infections annually, leading to serious health consequences and death. Mitochondria are membrane-bound organelles found in almost all eukaryotic cells and play an important role in cellular metabolism and energy production, including pathogenic fungi. These organelles possess their own genome, the mitochondrial genome, which is usually circular and encodes proteins essential for energy production. Variation and evolutionary adaptation within and between species’ mitochondrial genomes can affect mitochondrial function, and consequently cellular energy production and metabolic activity, which may contribute to pathogenicity and drug resistance in certain fungal species. This review explores the link between the mitochondrial genome and mechanisms of fungal pathogenicity and drug resistance, with a particular focus on Cryptococcus neoformans and Candida albicans. These insights deepen our understanding of fungal biology and may provide new avenues for developing innovative therapeutic strategies.